NFB-07. Meningiomatosis in an adolescent with TRAF-7 mutation related syndrome. (3rd June 2022) - Torres, Marleni; Jackson, Nicole; O'Farrell, Candelaria; Maher, Ossama; Niazi, Toba; Raghed, John; Khatib, Ziad
Abstract: BACKGROUND: Meningiomas are rare primary brain tumors in the pediatric population, associated with multiple genetic mutations. Recent description of mutations in the TRAF7gene, a pro-apoptotic E3 ubiquitin ligase, have been found in up to one quarter of non NF-2 tumors. TRAF is downregulated in human keratinocytes after inhibition of the PI3K/AKT/mTOR signaling. Germ-line mutations in this gene are associated with facial, cardiac malformations, variable intellectual deficiency, and musculoskeletal abnormalities. OBJECTIVE: We report a case of meningiomatosis in an adolescent with TRAF 7 mutation. CASE PRESENTATION: A 17 yo female with complex medical history that includes syndactyly of the left foot, small hands and digits, congenital heart disease, overgrowth of the right lower extremity with lipomatous subcutaneous tumors, connective tissue disorder variant mutation of unknown significance in the gene Col11A2, conductive hearing loss developed meningiomas of both optic nerves requiring decompression and unroofing on two separate occasions, with associated blindness. MRI brain showed bilateral optic nerve sheath enhancement, dysplasia of the corpus callosum, mild hemimegalencephaly, inter-hemispheric fissure 1.5 cm meningioma, bilateral enhancement of internal auditory canals as well as trigeminal and glossopharyngeal nerve, consistent with menigiomatosis. Pathology showed a grade I meningioma with a TRAF7 p.G536S detected by performing a 500 genomic panel (UCSF500). She was started on Everolimus and Bevacizumab. CONCLUSION: Recurrent multiple meningiomas represent a treatment challenge for neuro-oncologists. The evolving understanding of the genetics of these tumors has improved our understanding of their pathogenesis as well as treatment. TRAF 7 mutations are associated with non-NF-2 meningiomas, and distinct phenotypic features. Germ-line testing should be considered in patients with associated malformations, as targeted therapy may improve patient outcomes.